2018
DOI: 10.1136/gutjnl-2018-316948
|View full text |Cite
|
Sign up to set email alerts
|

Enterocolitis due to immune checkpoint inhibitors: a systematic review

Abstract: Immune checkpoint inhibitors targeting cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) and programmed death-1 (PD-1)/ligand are increasingly used to treat several types of cancer. These drugs enhance antitumour T-cell activity and therefore induce immune-related adverse effects (irAE), of which gastrointestinal (GI) irAE are among the most frequent and severe. This systematic literature review summarises the clinical manifestations, management and pathophysiology of GI irAE due to immune checkpoint inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
156
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 131 publications
6
156
0
3
Order By: Relevance
“…All colonic biopsy samples showed the predominance of CD4 immunostaining, while a recent report has shown that colonic mucosal lymphocytes are CD8 + predominant in nivolumabinduced colitis. 3 This result suggested that the immunological response is mostly activated by CD4 + T cells in our case.…”
supporting
confidence: 53%
“…All colonic biopsy samples showed the predominance of CD4 immunostaining, while a recent report has shown that colonic mucosal lymphocytes are CD8 + predominant in nivolumabinduced colitis. 3 This result suggested that the immunological response is mostly activated by CD4 + T cells in our case.…”
supporting
confidence: 53%
“…Diarrhoea is the most common clinical presentation for a GI‐irAE, with most patients showing histological evidence of enterocolitis . The incidence of diarrhoea is reported to be up to 13% for anti‐PD‐1/PD‐L1 therapy and 35% for anti‐CTLA‐4 therapy . Severe enterocolitis, which is one of the most frequent severe irAEs, is principally caused by anti‐CTLA‐4, and, in rare cases, leads to perforation and death .…”
Section: Introductionmentioning
confidence: 99%
“…2 The incidence of diarrhoea is reported to be up to 13% for anti-PD-1/PD-L1 therapy and 35% for anti-CTLA-4 therapy. 2,[5][6][7] Severe enterocolitis, which is one of the most frequent severe irAEs, is principally caused by anti-CTLA-4, and, in rare cases, leads to perforation and death. 2,8 Patients may also experience abdominal pain, nausea, and/or vomiting; haematochezia and fever are less frequent symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of diarrhea had been reported to be 12.1-13.7% for anti-PD-1 and 30.2-35.4% for anti-CTLA-4, whereas the incidence of colitis had been reported to be 0.7-1.6% for anti-PD-1, 5.7-9.1% for anti-CTLA-4, and 13.6% for the combination of both agents [8]. The endoscopic findings of irColitis closely resemble those of ulcerative colitis and include erythema, loss of vascular pattern, erosions, ulcerations, and luminal bleeding [4].…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, acute colitis can present as mononuclear cell and neutrophil infiltration of the lamina propria [9]. Blood examination and stool analysis should be carried out to rule out enteropathogens such as CMV and C. difficile [5,8].…”
Section: Discussionmentioning
confidence: 99%